2016
DOI: 10.3348/kjr.2016.17.5.789
|View full text |Cite|
|
Sign up to set email alerts
|

Endovascular Repair of Blunt Popliteal Arterial Injuries

Abstract: ObjectiveTo evaluate the feasibility and effectiveness of endovascular repair for blunt popliteal arterial injuries.Materials and MethodsA retrospective analysis of seven patients with clinical suspicion of popliteal arterial injuries that were confirmed by arteriography was performed from September 2009 to July 2014. Clinical data included demographics, mechanism of injury, type of injury, location of injury, concomitant injuries, time of endovascular procedures, time interval from trauma to blood flow restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…108 Covered stents, including the Viabahn (W. L. Gore & Associates, Inc), 111,112 Fluency (Bard), 92,107,113 Jostent (Abbott), 111 iCast (Atrium), 114 WALLGRAFT (Boston Scientific, Inc), 115 and Passager (Boston Scientific) 116 have been described to treat occlusions, transections, pseudoaneurysms, extravasation, and AC fistulas. Bare metal stents, including the Xceed (Abbott) 69 and Lifestent (Bard) 109 have been used to treat transections and pseudoaneurysms.…”
Section: Lower Extremitymentioning
confidence: 99%
See 1 more Smart Citation
“…108 Covered stents, including the Viabahn (W. L. Gore & Associates, Inc), 111,112 Fluency (Bard), 92,107,113 Jostent (Abbott), 111 iCast (Atrium), 114 WALLGRAFT (Boston Scientific, Inc), 115 and Passager (Boston Scientific) 116 have been described to treat occlusions, transections, pseudoaneurysms, extravasation, and AC fistulas. Bare metal stents, including the Xceed (Abbott) 69 and Lifestent (Bard) 109 have been used to treat transections and pseudoaneurysms.…”
Section: Lower Extremitymentioning
confidence: 99%
“…Popliteal stents are beginning to see use in popliteal aneurysms, 106 with the suggestion that they may be equivalent to open bypass. Justifications for pursuing endovascular rather than open repair for popliteal injuries in blunt, penetrating, and iatrogenic trauma include a concomitant, vertical incision for orthopedic procedures, 107 concern for placing prosthetic into a contaminated wound, 108 desire to decrease time to revascularization, 109 or tissue disruption due to trauma. 110 Devices and techniques use vary.…”
Section: Poplitealmentioning
confidence: 99%
“…Stent patency rates were 75.3% at 12 months, 61.9% at 24 months, and 55.7% at 48 months. Similarly, Zhong et al reported in-stent thrombosis in one out of seven patients who underwent endovascular stenting to the popliteal artery at 18 months following the initial injury [ 15 ]. Although in-stent thrombosis appeared higher in these patients, most of these complications were amenable to endovascular recannulation.…”
Section: Discussionmentioning
confidence: 99%
“…This may be especially true in regions where open surgery would cause iatrogenic complications (5). Endovascular interventions in extremity trauma have been associated (19,23,24). Iliac artery injuries can be quite severe and are associated with significant mortality rates upwards of 40% (25), necessitating the need for rapid intervention.…”
Section: Endovascular Techniques In Extremity Traumamentioning
confidence: 99%